How do intensive care nurses assess patients’ pain? - (:unkn) unknown (John Wiley and Sons Inc, 2003)
• Identification and evaluation of pain in critical care patients may be difficult because of communication problems. Moreover, at present there are very few nursing studies that examine the attitudes of critical care nurses towards the assessment of patients’ pain • This study was designed to determine the approach of critical care nurses towards assessing patients’ pain levels, and to evaluate the problems in nursing diagnosis of those having difficulty in articulating their pain symptoms • We used a questionnaire to assess nurses attitudes to patients’ pain. The study sample consisted of 91 critical care nurses who were recruited between January and February 2002. The results suggest that patient pain was considered undesirable by 44% of nurses. About 70·3% of the nurses reported resorting to administering analgesics to relieve their patients’ pain • Some 57·1% of nurses stated that they would have investigated whether the patients had really been experiencing pain, prior to administering the prescribed analgesics to patients • Some 85·7% of the sample indicated that the patients themselves would make the most accurate evaluation of their pain. The data suggested that 39·6% of nurses did not know how to evaluate pain symptoms in critical care patients suffering from complicated problems, and that 37·4% evaluated pain by monitoring the patients’ behaviours • The study demonstrated that most of the critical care nurses did not know how to evaluate pain in patients having communication problems. The paper concludes by suggesting that there is a clear need to address nursing education and training with regard to evaluation and management of patients’ pain whilst in critical care environment. © 2003, John Wiley and Sons Inc. All rights reserved.
Keywords: Critical care/ intensive care; Intensive care nurse; Nursing interventions; Pain; Pain assessment